Modulation of foraging-like behaviors by cholesterol-FGF19 axis - Alyssa Huang; Matthew T. Maier; Eirini Vagena; Allison W. Xu (Cell & Bioscience, 2023)
Abstract Background Foraging for food precedes food consumption and is an important component of the overall metabolic programming that regulates feeding. Foraging is governed by central nervous system neuronal circuits but how it is influenced by diet and hormonal signals is still not well understood. Results In this study, we show that dietary cholesterol exerted suppressive effects on locomotor activity and that these effects were partially mediated by the neuropeptide Agouti-related protein (AgRP). High dietary cholesterol stimulated intestinal expression of fibroblast growth factor 15 (Fgf15), an ortholog of the human fibroblast growth factor 19 (FGF19). Intracerebroventricular infusion of FGF19 peptide reduced exploratory activity in the open field test paradigm. On the other hand, the lack of dietary cholesterol enhanced exploratory activity in the open field test, but this effect was abolished by central administration of FGF19. Conclusions Experiments in this study show that dietary cholesterol suppresses locomotor activity and foraging-like behaviors, and this regulation is in part mediated by AgRP neurons. Dietary cholesterol or the central action of FGF19 suppresses exploratory behaviors, and the anxiogenic effects of dietary cholesterol may be mediated by the effect of FGF19 in the mouse brain. This study suggests that dietary cholesterol and intestinal hormone FGF15/19 signal a satiating state to the brain, thereby suppressing foraging-like behaviors.